Generation "P": Philippines' millennial impact entrepreneurs - Tuliao, Jinky (Institutional Knowledge at Singapore Management University, 2017)
"Millennials"—broadly defined as those born between 1980 and 2000— are a dynamic driving force behind any country’s economic progress, but particularly so in the Philippines. Making up about 50 per cent of the national population, Philippine millennials are mainly employed in micro, small and medium enterprises (MSMEs), which in turn account for over 99 per cent of all local businesses.